Application of signed graph in amino acid network - Adil Akhtar; Nasrin Irshad Hussain (Network Biology)
This article is aimed to construct a model related to protein structure and amino acids viz., Brandstein and Tooze's condition. To study Brandstein and Tooze's condition we have considered signed graph in amino acids. For this we have constructed a network structure, where the link is based on the one point mutation of codons of corresponding 20 different essential amino acids. To study this we have considered signed graph in amino acids and consider two cases. In the first case positive sign is assigned to an edge if both the amino acids are either hydrophobic or hydrophilic, otherwise negative sign is assigned. And in the second case positive sign is assigned to an edge if one amino acid is hydrophobic and the other is hydrophilic, otherwise negative sign is assigned.